Gentrification and the suburbanization of poverty: changing urban geographies through boom and bust periods. Issue 1 (2nd January 2018) - Hochstenbach, Cody; Musterd, Sako
ABSTRACT: Many postindustrial cities across Europe and other contexts are marked by growing social–spatial inequalities, housing liberalization, and gentrification, which limit the housing options of low-income households. We investigated changes in the residential moves of different low-income households (working poor, low-to-middle income, and unemployed) in the Amsterdam and Rotterdam urban regions for the time period 2004–2013. We found an overarching trend for the suburbanization of poverty toward the urban peripheries and surrounding regions. While this trend appears to be relatively crisis resistant in the tight Amsterdam housing context, it is more cyclical in Rotterdam and has slowed following the global financial crisis. Low-to-middle income and unemployed households are increasingly moving to the urban regions surrounding cities, particularly to higher density satellite towns. Nevertheless, a growing number of working poor households remain highly urbanized, employing various coping strategies to acquire housing. This paper reveals how the suburbanization of poverty is both a direct process of poor households moving from city to suburb, and a broader indirect process caused by exclusionary mechanisms such as the decreasing accessibility and affordability of inner-urban neighborhoods, which reflect broader changes in the geography and socioeconomic patterning of urban regions.